Cross-species amplification and polymorphism of microsatellite loci in Asian bovidae - Hishida, O.; Hanotte, Olivier H.; Verjee, Y.; Tanka, K.; Namikawa, T.; Teale, A.J.; Rege, J.E.O. (Japanese Society of Zootechnical Science, 1996)
Microsatellite loci are tandem repeats of short DNA sequences (1-5bp). Polymorphism in these loci results from variation in the number of repeat units. Microsatellites are numerous and dispersed among the chromosomes in all eukaryotic genomes. They are now the markers of choice for genome mapping, pedigree analysis and the study of genetic diversity of livestock. Conservation of flanking sequences of microsatellites allows primer sets to be used across related species. For example, 40 percent of microsatellites isolated in cattle Bos taurus amplify polymorphic loci in goat Capra hircus (Kemp et al 1995, Pepin et al. 1995) and 50 percent of cattle microsatellites amplify polymorphic loci in sheep Ovis aries (Moore et al 1994, Kemp et al 1995). It was Reported in cattle, the isolation and characterisation of 97 microsatellites (Kemp et al. 1995). It is Reported here the cross-species amplification of a subset of 52 loci in two species of Asian bovidae: the swamp and river types of water buffalo Bubalis bubalis and the Bali cattle Bos banteng.